Skin temperature recovery from cold provocation in workers exposed to vibration: a longitudinal study. Issue 12 (21st November 2003) - Cherniack, M; Brammer, A; Meyer, J; Morse, T; Peterson, D; Fu, R
Abstract : Background: Vibration white finger (VWF) is characterised by arterial hyperresponsiveness and vasoconstriction following cold provocation. Several years after of removal from exposure, most subjects show improved finger systolic blood pressure (FSBP) under conditions of cold challenge, but continue to report cold hands and finger blanching. Aims: To assess the underlying reasons for the persistence of cold symptoms. Methods: A total of 204 former users of pneumatic tools with cold related hand symptoms were evaluated and then re-evaluated a year later. Symptoms were evaluated using the Stockholm Workshop Scale. Finger systolic blood pressure per cent (FSBP%) was assessed by comparing digital blood pressure in a cold provoked and normalised state. Fingertip skin temperature was measured during cooling and occlusion and during rewarming and recovery. Results: There were dramatic improvements in FSBP% (14.3 mm Hg %), modest improvement in recovered skin temperature (0.86°C), and no change in symptom stage. When the most symptomatic subjects (n = 75) were compared with the less symptomatic subjects (n = 129), there were similar inter-test improvements in FSBP%. Skin temperature recovery improved in the less symptomatic (+1.49°C), but did not change in the most symptomatic group (−0.12°C). However, the more symptomatic group had higher temperatures at the initial test, thus qualifying the result. Conclusions: Skin temperature recovery after cold challenge in subjects with VWF remains reduced in the symptomatic subjects several years after exposure removal. This is evident even when blood pressure has increased in the setting of cold provocation. Results suggest that in VWF, the dermal circulation remains impaired, even after the restoration of arterial blood pressure in the digits.